Long-Term Survival in Canine Hepatosplenic T-Cell Lymphoma Treated with Toceranib Phosphate Following Splenectomy: A Case of Atypical Lymphoma - Makoto Akiyoshi; Masaharu Hisasue; Midori Goto Asakawa; Sakurako Neo (Veterinary Sciences, 2024)
Toceranib phosphate (toceranib) is approved for canine mast cell tumor treatment. However, no long-term response to toceranib in canine HSTCL has been reported. Here, we describe a case of a 10-year-old castrated mixed-breed dog that presented with a 3-month history of weight loss, polydipsia, and polyuria. The clinicopathological and imaging abnormalities included icterus, biliary obstruction, and splenomegaly with multiple diffuse splenic hypoechoic nodules. On day 21, a cholecystectomy was performed to remove the obstruction, followed by a liver biopsy and splenectomy. Cytology of the spleen and liver showed many small lymphocytes with intracytoplasmic granules (sGLs). Splenic and hepatic infiltration of neoplastic CD3/granzyme B-positive small cells and lymphocytic cholecystitis with granzyme B-negative small cells were noted. T-cell receptor gene clonal rearrangements were observed in the liver tissues. The dog was diagnosed with a hepatosplenic T-cell lymphoma (HSTCL) of sGLs concurrent with lymphocytic cholecystitis. The icterus resolved after surgery, but there was progressive elevation of liver enzyme levels. Toceranib was administered from day 39, resulting in decreased liver enzyme levels, and the dog remained in good condition. The dog stayed in remission after toceranib administration and survived for 460 days. Toceranib should be considered an effective treatment option for canine HSTCL.